Test procedures to assess somatosensory abnormalities in individuals with neck pain: a systematic review of psychometric properties. (2nd November 2018) - Alqarni, Abdullah; Manlapaz, Donald; Baxter, David; Tumilty, Steve; Mani, Ramakrishnan
Abstract: Background: Test procedures that were developed to assess somatosensory abnormalities should possess optimal psychometric properties (PMPs) to be used in clinical practice. The aim of this systematic review was to evaluate the level of evidence for PMPs of those test procedures, administered to identify somatosensory abnormalities in individuals with neck pain. Methods: A comprehensive electronic literature search was conducted in seven databases from inception to July 2018. The Quality Appraisal for Reliability Studies (QAREL) checklist and the COSMIN tool were used to assess risk of bias of the included studies. Level of evidence was determined based on two components: the methodological quality of included studies and the quality of statistical measures of measurement properties for each testing procedure. Results: Eighteen studies related to neck pain were included. The majority of included articles were considered to be of insufficient methodological quality to ascertain the PMPs of each testing procedure investigated. However, adequate methodological studies indicated that there is moderate level of evidence for the reliability and discriminative validity of the electrical current perception threshold using the neurometer CPT/C. In addition, the hand-held digital pressure algometer (Wagner FDX-25 Greenwich, CT) has moderate evidence for the reliability and responsiveness. Conclusions: This systematic review identified that the hand-held digital pressure algometer and the neurometer has acceptable PMPs. Future research should include adequate sample size, description of the assessors, and inclusion of blinding processes. Further research with standardized protocols is recommended to investigate the predictive ability and responsiveness of reported test procedures to ensure their extended clinical utility.